WORK EMOTION MANAGEMENT REVIEWED FROM PERSONALITY TYPE - Mulyono, Puput; Purnomo, Singgih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to determine the differences in emotional management in salespeople who have extrovert and introvert personality types. The subjects of the study were 92 salespeople at Department Store X (82 women; 10 men), aged between 18-40 (average age 22 years). In general, the subjects had a high school education background or equivalent, with an average work period of 2.5 years. Data collection used two scales, namely the Eysenck Personality Questionnaire or EPQ (22 items; α = 0.865) and the Emotional Labor Scale (11 items; α = 0.787). The results of data analysis using the t-test showed that the average emotional labor of salespeople who tended to have an extrovert personality type (Mintrovert = 36,08; Mextrovert = 33,67, t = 3,50; P = 0,001) Thus, it can be concluded that salespeople with a tendency towards an introvert personality type are more capable of managing emotions according to job demands than salespeople with a tendency towards an extrovert personality type.